SOSIALISASI HUKUM TENTANG FUNGSI KEPALA DESA DALAM RANGKA PENERAPAN RESTORATIVE JUCTICE DI PEMERINTAHAN DAERAH SELARAS DENGAN PRINSIP NEGARA HUKUM INDONESIA DI DESA MULUR KECAMATAN BENDOSARI KABUPATEN SUKOHARJO - Arga Baskara,; Febri Atikawati Wiseno Putri, (JURNAL PENGABDIAN MANDIRI, 2025)
The function of village heads in the implementation of the restorative justice concept in Indonesia, particularly at the village governance level. Restorative justice is understood as a legal approach that emphasizes restoring social relations among offenders, victims, and the community through dialogue and mutual agreement. This study employs a descriptive qualitative method based on literature review, regulatory analysis, and documentation of a legal awareness program conducted in Mulur Village, Bendosari District, Sukoharjo Regency. The findings indicate that the principle of the Indonesian rule of law, grounded in Pancasila, promotes justice that is not only retributive but also substantive and socially equitable. Village heads play a crucial role in maintaining social harmony, strengthening deliberative democracy at the village level, and acting as a bridge between the community and law enforcement agencies, in accordance with Law No. 6 of 2014 on Villages and the new Criminal Code (Law No. 1 of 2023). However, to strengthen this role, regulatory support, legal education, and synergy with law enforcement institutions are required. Therefore, village heads can become key actors in realizing restorative justice that is humanistic, democratic, and inclusive in line with Pancasila values